Distributed Generation installed by the Phasor Measurement Unit to improve voltage - Azriyenni Azhari Zakri; Rangga Eka Saputra; Makmur Saini; Hidayat Hidayat (SINERGI, 2022)
This study is intended to design a system connected to the Distributed Generation (DG) sourced from solar cells, using Matlab/Simulink. A Phasor Measurement Unit (PMU) is installed in the DG system to monitor the phasor voltage and current. Furthermore, the system comprises four buses with two 20 kV load voltages, two amplifying transformers, and four transmission lines. The DG's role is to keep the power supply to the load stable and improve power efficiency by reducing power losses on the network. However, in this network, the DG increases the current on each bus. Thus, affecting voltage increase on each bus, consequently increasing the stress experienced by both loads. The DG-connected system simulation on PMU-3 & PMU-4 has a minute error value of 0.02% and is slightly higher than the unconnected simulation. This comparison also shows the positive sequence values of the phasor currents as well as phasor voltages before and after the DG connection. The DG system connected to the PMU has monitored voltage and current for PLN and DG systems based on the simulation results. Therefore, installing the DG can increase the line voltage, especially on the load.